FICHTES ERZIEHUNGSLEHRE ALS ERSTE LOGISCHE BEGRÜNDUNG DER VORBILDERZIEHUNG. EINE UNTERSUCHUNG IM KONTEXT DER INTERPRETATIONEN VON FICHTES PÄDAGOGIK IN JAPAN - Kumamoto, Yasuhiro (Daimon Revista Internacional de Filosofia, 1994)
Fichte’s educational theory used to be interpreted in Japan only as a kind of national education (Volkserziehung), because it was considered focussing on his «Adresses to the German Nation» and the few other popular essays. There is a little harvest in Japan among those which have tried to construct Fichte’s educational theory on the basis of his philosophical theory. This miserable result of the study on Fichte’s educational theory comes mainly from the fact that the investigations of Fitchte’s philosophy and pedagogy are separated in Japan. The made pedagogy very lightly in the domain of philosophy on the one hand, and pedagogical investigation dosen’t come to precise understanding of philosophical foundation on the other. Therefore, the task of this paper is set on fixing Fichte’s philosophy and pedagogy as unified one. And by means of performing this consideration we can bring out a new reading of Fichte’s pedagogy which has never been reached by clinging to the nationalistic explanation of his pedagogy. We take the fundamental point of Fichte’s philosophical theory is the freedom and the education is the most important methode for realization of the feedom. In addition, we make the essence of Fichte’s educational theory clear depending upon the elucidation of the meaning of the concept «freedom». Acording to Fichte, a free will must be raised to the good will that can choose always the good without fail from «The arbitrariness» that is driven by selfish desire. This good will is the true free will. This uplift is possible through «the ideal educatio» (Vorbilderziehung). This ideal education fosters «a pure pleasure in the good» (ein reines Wohlgefallen am Guten) that is «intellectual pleasure», so to speak. We would like to explain the process and the meaning of this ideal education. Fichte’s true historic achievement in pedagogy is to found «the ideal education» by the precise logic. If we grasp Fichte’s educational theory in this context, we can also understand the meaning of «national education» and «isolating education» more cleary and exactly than over.